Academic Senate Minutes 2011-03-10 - Academic Senate:::::::::
Agenda approved. Minutes delayed. Two curricular revisions from Kinesiology approved. Chair-Elect Report. Staff Report. Special Presentation: New Student Center. Request for endorsement of Report with recommendations from FSSP regarding the survey of faculty needs in support of externally funded research and scholarship referred back to FSAC for endorsement statement. Senate Diversity Subcommittee Report. Special Report: President's Diversity Council Diversity Strategic Plan. CFA Report. Special Guest: Mayor Gina Belforte, Rohnert Park.